THE CONCEPT AND ANALYSIS OF LITERARY TEXT - Shukrulloyeva Janona Shuxrat qizi (Web of Journals Publishing, 2024)
A measure of literary text perfection is its level of artifacts. In literary text, we distinguish between content and form. artifacts are the artistic quality of a work consisting of an important content and a harmonious combination of the perfect form that corresponds to it. Only a work with complete compatibility, harmony between all its components can be called highly artistic. Artisticism as the nucleus of literary literature directly defines the way it is studied, that is. analysis. Analysis of text is a method of understanding it, reviewing content elements, identifying topics, ideas, motives, methods of visually expressing them, as well as tools for creating images. In other words, it is a disclosure of the artifacts of the text.
Keywords: artistic text, poem, analysis, interpretation, contextual analysis, immanent analysis, comparison, verbal tahliol, written analysis, scientific (philosophical) and academic didactic analysis, analysis principles.